A Retrospective Study One-Year Survey from COVID-19: Three Waves and Three Patterns in Italy - Olga Kolesova; Flaminia Tomassetti; Paola Cerini; Laura Caldarelli; Laura Marullo; Fulvio Cantore; Elena Zocca; Maria Loredana Frassanito; Maria Teresa Quarantelli; Massimo Pieri; Graziella Calugi (Masters Program in Public Health, 2021)
Background: Since December 2019 an unprecedented coronavirus pandemic (COVID-19) in Italy and in all the world, has been spreading. This study is a retrospective overview of Italian popula